The Influence of PUBG Mobile Online Game on the English Learning - Ahmad Siraj Julian (Universitas Serambi Mekkah, 2022)
This study aims to determine the English learning achievement of students playing the PUBG Mobile online game and the effect of the PUBG Mobile online game on students' English learning. The method used in this study was a descriptive design. The participants of this study were selected using purposive sampling technique, in which 15 students from class XIa, and 15 students from class XIb. This study used documents (English test scores) and a Likert scale questionnaire as instruments. This study found that the average English achievement score of class XI MAN 2 Banda Aceh students who played the PUBG Mobile online game was 62, in the unsatisfactory category. Besides, the influence of the PUBG Mobile online game on the English learning of class XI MAN 2 Banda Aceh students had 90% negative effect. Therefore, it can be concluded that the PUBG Mobile online game had a negative impact on the students' English learning achievement.